Impact of Hepatitis C Virus on the Circulating Levels of IL-7 in HIV-1 Coinfected Women. (1st February 2016) - Kerzerho, Jerome; McIlvaine, Elizabeth J.; Anthony, Patricia; Mack, Wendy J.; Wang, Chia-Hao; Frederick, Toni; Operskalski, Eva; Chen, Zhi; Al-Harthi, Lena; Landay, Alan; Young, Mary A.; Tien, Phyllis C.; et al.
Abstract : Objectives: Hepatitis C virus (HCV) infection causes an alteration in T-cell maturation and activation in patients coinfected with human immunodeficiency virus (HIV). Because interleukin 7 (IL-7) is a major cytokine controlling T-cell homeostasis, we analyzed the potential influence of HCV coinfection on circulating IL-7 levels in HIV-infected women before and after highly active antiretroviral therapy (HAART). Design and Methods: This prospective study included 56 HIV monoinfected, 55 HIV/HCV coinfected without HCV viremia, 132 HIV/HCV coinfected with HCV viremia, and 61 HIV/HCV-uninfected women for whom plasma levels of IL-7 were determined by enzyme-linked immunosorbent assay at 1 or more follow-up visits before and after HAART. Cross-sectional analyses of the associations between plasma IL-7 levels and HCV infection, demographic, clinical, and immunologic characteristics were evaluated using univariate and multivariate linear regression models before and after HAART. Results: In multivariate models, IL-7 levels were significantly higher in coinfected HCV viremic women than in HIV monoinfected women (multiplicative effect = 1.48; 95% confidence interval: 1.01 to 2.16; P = 0.04) before HAART, but were similar between these two groups among women after HAART. In addition to HCV viremia, higher IL-7 levels were associated with older age ( P = 0.02), lower CD4 + T-cell count ( P = 0.0007), and higher natural killer T-cell count ( P = 0.02) in women before HAART. Among HAART-treated women, only lower CD4 + T-cell count was significantly associated with IL-7 level ( P = 0.006). Conclusions: Our data demonstrate that in HIV-infected women, circulating levels of IL-7 are strongly associated with CD4 + T-cell depletion both before and after HAART. Our data also demonstrate that HCV viremia increases circulating IL-7 levels before HAART but not after HAART in coinfected women. This suggests that the effect of HCV on lymphopenia is abrogated by HAART.